Potensi Pengembangan Budidaya Tambak Tradisional di Daerah Pesisir Paojepe, Kabupaten Wajo, Sulawesi Selatan - Tri Widiyanto; Y. Purwanto; Bambang T Sudiono; Vidya Indanvati (The Ethnobiological Society of Indonesia, 2005)
Study on potential development of fishpond (aquaculture fisheries) based on the condition of water quality in Paojepe coast, Wajo Regency, South Sulawesi was carried out in 1999 and 2000. This study aims in developing fishpond production in that area and improving the awareness of the farmers to avoid environmental destruction caused by quite high abration. The results show that the current fisheries system is a traditional system with very low productivity. The introduction of technology of water and sediment management can be done in order to increase fishpond productivity. Referring to some parameters of the water such as its physics, chemistry and biology, the area has a good potential to develop fishpon on